DEVELOPMENT OF THE COMPOSITION AND STUDY OF THE MICROBIOLOGICAL PURITY OF THE ANTI-ANALYZED COLLECTION “MIGLIKAL” - Usmanov, Ulugbek Khusanovich (International Journal of Psychosocial Rehabilitation, 2020)
In diseases of the gastrointestinal tract, in general, and in peptic ulcer of the stomach and duodenum, in particular, medicinal plants are widely used because of their wound healing, hemostatic, antispasmodic, astringents, which improve digestion function. The problem is successfully solved by the use of multicomponent herbal compositions or fees.At the same time, in the production of medicinal charges, it is necessary to assess the probability of the possibility of producing poor-quality medicinal charges and improve their control system, ensuring quality assurance. The safety and harmlessness of the drug collection directly depends on its microbiological parameters. This article presents the results of a study of the microbiological purity of the anti- ulcer collection “Miglikal” in accordance with the State Pharmacopoeia XI, no. 2, p. 193 and amendments #2.